Predictive Relationships between Chronic Pain and Negative Emotions: a Four Month Daily Process Study Using Therapeutic Interactive Voice Response (TIVR) - Naylor, Magdalena R. (2011)
This paper examines temporal relationships between negative emotions and pain in a cohort of 33 patients with chronic musculoskeletal pain enrolled in a telephone-based relapse prevention program [Therapeutic Interactive Voice Response (TIVR)], following 11 weeks of group Cognitive Behavioral Therapy (CBT). Patients were asked to make daily reports to the TIVR system for four months following CBT. Patients’ daily reports were analyzed with path analysis to examine temporal relationships between three emotion variables (anger, sadness and stress) and two pain variables (pain and pain control). As expected, same-day correlations were significant between emotion variables and both pain and pain control. The lagged associations revealed unidirectional relationships between pain and next-day emotions: increased pain predicted higher reports of sadness the following day (p<0.05). Conversely, increased pain control predicted decreased sadness and anger the following day (p<0.05). Unlike some previous studies, this study did not reveal that an increase of negative emotions predicted increased next-day pain. We speculate that CBT treatment followed by the relapse prevention program teaches patients how to modulate negative emotions such that they no longer have a negative impact on next-day pain perception. The clinical implications of our findings are discussed.